Nature tourism transformation and development - Rawat, Taj (New Delhi Discovery Publishing House, 2009)
With reference to Uttaranchal and Himachal Pradesh states of India
Includes bibliographical references (p. [175]-179) and index
Keywords: Ecotourism -- India -- Himachal Pradesh; Ecotourism -- India -- Uttaranchal; Himachal Pradesh (India) -- Description and travel; Uttaranchal (India) -- Description and travel